2011
DOI: 10.1007/s10571-011-9683-4
|View full text |Cite
|
Sign up to set email alerts
|

BanI/D13S141/D13S175 Represents a Novel Informative Haplotype at the GJB2 Gene Region in the Iranian Population

Abstract: Non-syndromic sensorineural hearing loss (NSHL) represents the most common cause of hearing loss in the Iranian patients. In view of the large numbers of mutations identified in GJB2, mutations analysis of the gene has been time-consuming and cost-ineffective. Alternatively, molecular markers that are highly linked to the GJB2 gene have proven to be useful in carrier detection and prenatal diagnosis of NSHL families. These markers usually show a population-dependent-based haplotype frequency. However, to date,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…The studies of LD in different populations indicated that LD among normal polymorphic markers differs in various populations of the world (Goldstein and Weale, 2001). Therefore, it is necessary to estimate LD between a pair of loci in every population independently (Rezaei and Vallian, 2011;Vallian and Fazeli, 2011). In the present study, the allele and haplotype frequency as well as LD of three markers in the FMR1 gene region, including DXS998, DXS548, and FRAXAC1, were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The studies of LD in different populations indicated that LD among normal polymorphic markers differs in various populations of the world (Goldstein and Weale, 2001). Therefore, it is necessary to estimate LD between a pair of loci in every population independently (Rezaei and Vallian, 2011;Vallian and Fazeli, 2011). In the present study, the allele and haplotype frequency as well as LD of three markers in the FMR1 gene region, including DXS998, DXS548, and FRAXAC1, were investigated.…”
Section: Introductionmentioning
confidence: 99%